Current collector with open structure, pole piece and electrochemical device
By using a combined structure of a dense conductive layer and an open structure insulating support layer in the composite fluid, a three-dimensional conductive network is formed, which solves the problem of degradation of the conductive properties of the composite fluid at high temperatures, and achieves high energy density and good mechanical properties.
Patent Information
- Application Number
- CN202420429004.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2034-03-06
AI Technical Summary
The existing composite liquid collector is prone to melting, deforming or breaking of the resin layer at high temperatures, resulting in a decrease in conductivity, affecting the battery's performance and safety. At the same time, the low conductivity limits the battery's discharge rate and power density.
The combined structure of a dense conductive layer and an insulating support layer is adopted. The insulating support layer has an open structure that penetrates along the thickness direction. The connection between the conductive layer and the insulating support layer is through the conductive reinforcement layer to form a three-dimensional multi-point conductive network.
It improves the mechanical properties, mechanical properties and conductivity of the current collector, enhances the preparation and use reliability of the battery, improves the electrochemical properties and weight energy density, and improves the high-rate charging and discharge performance and cycle life of the battery.
Smart Images

Figure CN222581177U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the field of electrochemical current collectors, in particular to a current collector, a pole piece and an electrochemical device with an open structure. Background Art
[0002] The current collector is an important component of lithium-ion batteries. The lighter the weight of the current collector, the more conducive it is to obtain high energy density. The current collectors are mainly divided into two categories: metal foil current collectors and composite current collectors. Metal foil current collectors are mainly copper foil and aluminum foil. The thickness of copper foil generally used is 4-8μm, and the thickness of aluminum foil is 8-10μm, which has reached the ultimate level of manufacturability of lithium-ion batteries. Reducing the thickness of copper foil or aluminum foil will cause the current collector to be brittle and easy to break, which cannot meet the mechanical performance requirements of the current collector, so it is impossible to further increase the battery energy density by reducing the thickness of the metal current collector.
[0003] The composite current collector is made of a polymer high molecular layer as a support layer, and a metal conductive layer is deposited on both sides of the polymer high molecular layer. For example, for a copper-based composite current collector, 4.5μm PP can be used as a substrate, and a 1μm thick copper coating can be formed on both sides of the PP by electroplating and / or sputtering. For an aluminum-based composite current collector, 6μm PET can be used as a substrate, and a 1μm thick aluminum coating can be formed on both sides of the PET by evaporation and other methods. Since the thickness of the metal conductive layer is greatly reduced compared to the metal foil current collector, and the density of the polymer high molecular layer is low, the overall weight reduction effect is achieved, and it has good flexibility and high tensile properties.
[0004] However, in the existing composite current collector, the resin layer polymer macromolecule is used as the base material, and the conductive layer is formed into a very thin coating by evaporation and other methods. The resin layer usually has low thermal stability. When the battery temperature rises and approaches the melting point of the resin layer material, the internal resin layer may easily melt, deform or break at high temperature. This will cause the deposited metal conductive layer to break, the conductivity to decrease, and affect the performance and safety of the battery. At the same time, the conductive layer is located on both sides of the resin layer. Because the polymer macromolecule resin layer itself does not have conductivity, the metal conductive layers on both sides cannot be directly conductive, and additional conductive materials or conductive holes or edge coatings are required, resulting in relatively low overall conductivity. This may limit the discharge rate and power density of the battery. At the same time, it also increases the complexity of processing.
[0005] Chinese patent application CN115440987A discloses a current collector, which includes a first polymer layer, a metal foil layer and a second polymer layer stacked in sequence, and a plurality of through holes penetrating two opposite surfaces of the current collector in the stacking direction. The current collector can be effectively infiltrated by the electrolyte, improving the electrochemical consistency inside the current collector, and can also effectively inhibit the generation of lithium dendrites, avoid the generation of dead lithium, and improve the electrochemical performance and safety. The difference between the above technical scheme and the existing composite current collector is that the polymer layer is arranged on both sides of the metal foil, and the polymer layers on both sides can support the metal foil, thereby reducing the risk of melting of the single-side polymer layer. By setting through holes on the polymer layer and the metal foil layer, lithium ions can be effectively deposited in the internal space, avoiding the generation of lithium dendrites and improving the cycle performance. However, the through holes penetrate the metal layer on the one hand, and the discontinuity of the conductive structure on the other hand will greatly increase the resistance, increase the scattering and loss of current in the conductive layer, and affect the improvement of the cycle performance. More importantly, the through hole penetrates the three layers as a whole, and the conductive contact surface of the metal layer is only the cross-section of the through hole. The contact resistance is large, which will greatly reduce the conductive performance of the current collector.
[0006] Therefore, it is of great significance to develop a new type of composite current collector, maintain the higher energy density of the composite current collector relative to aluminum foil or copper foil and the original tensile properties of the composite current collector, improve the conductive properties of the composite current collector and avoid safety problems caused by the melting of the resin layer. Utility Model Content
[0007] The utility model overcomes the deficiencies in the above-mentioned prior art and provides a composite current collector, which has high mechanical properties and mechanical properties, and at the same time has good electrical conductivity and current collection properties, thereby being able to improve the preparation efficiency and reliability of the composite current collector, electrode plates and electrochemical devices during use, and is conducive to making the electrochemical device have high electrochemical properties and high weight energy density, and the preparation method is simple and efficient.
[0008] The composite current collector described in the utility model includes a dense conductive layer, and the dense conductive layer is provided with insulating support layers on both side surfaces opposite to each other in the thickness direction of the dense conductive layer. The insulating support layer has an open structure, and the open structure penetrates the insulating support layer along the thickness direction of the insulating support layer.
[0009] In the scheme of the utility model, the open structures only penetrate the insulating support layers where they are located, maintaining the integrity of the dense conductive layer. Therefore, on the one hand, the continuous conductive structure is retained, and on the other hand, its conductive contact surface is the sum of the pore surface areas of the entire open structure, which is much larger than the cross-sectional area of the through hole. Therefore, while having higher mechanical properties and mechanical properties, the current collecting and conductive properties of the collector are greatly improved.
[0010] Furthermore, the thickness D1 of the dense conductive layer is 0.5 μm-10 μm, preferably 1-6 μm, and more preferably 1-2 μm; the thickness D2 of the insulating support layer is 1 μm-10 μm, preferably 1 μm-6 μm, and more preferably 1 μm-4 μm.
[0011] Furthermore, the volume proportion θ of the open structure in the insulating support layer satisfies 0.1≤θ≤0.8, and preferably satisfies 0.2≤θ≤0.6.
[0012] Furthermore, the open structure is a quadrilateral (such as a parallelogram, a rectangle), a circle or a quasi-circular (such as an ellipse) hole.
[0013] Furthermore, the inner diameter or side length of the open structure is 1 μm-3 mm, preferably 1 μm-500 μm.
[0014] Furthermore, the distance between the open structures is 0.01 mm-5 mm, preferably 0.1-0.5 mm, and the spacing is distributed in equal spacing or non-equal spacing.
[0015] Furthermore, the insulating support layer includes N sub-support layers, N is an integer greater than or equal to 2, wherein the first sub-support layer is arranged in contact with the dense conductive layer, and the thickness dn of each sub-support layer gradually increases from the first sub-support layer to the Nth sub-support layer.
[0016] Furthermore, when N is an even number, the sum of the thicknesses of the 1st to N / 2nd sublayers d N / 2 Satisfy 0.1*D1≤d N / 2 ≤0.5*D1; when N is an odd number, the sum of the thicknesses of the 1st to (N-1) / 2 sublayers d N-1 / 2 Satisfy 0.08*D1≤d N-1 / 2 ≤0.4*D1.
[0017] In the process of the current collector being wound around the pole piece or folded to form an electrode, the above-mentioned multiple sub-support layers are arranged as an insulating support layer with a thickness gradually increasing from the inside to the outside, so that the bending stress of the insulating support layer when bending is dispersed to each sub-support layer, avoiding the requirement for the bending synchronization of the insulating support layer as a whole and the dense conductive layer. At the same time, since the thickness of the inner sub-support layer is small and does not exceed half of the thickness of the dense conductive layer, it is easy to bend during the bending process of the dense conductive layer and keep consistent with the dense conductive layer, and becomes a bending buffer area between the insulating support layer and the dense conductive layer.
[0018] Furthermore, the thickness of the two adjacent sub-support layers differs by 1-2 times. If the thickness of the two adjacent sub-layers differs too much, it may cause the bending stress of the outer layer and the inner layer to differ too much, and a good buffering progressive effect cannot be achieved.
[0019] Furthermore, nano inorganic fillers are distributed on the contact interface of each sub-support layer, and the distribution density of the nano inorganic fillers is 0.05-0.1 g / cm 3 .
[0020] Furthermore, the particle size of the nano inorganic filler is in the range of 80-150 nm.
[0021] Furthermore, the inorganic nanofiller is one or more of nano-silicon dioxide, nano-kaolin, and nano-barium sulfate.
[0022] Furthermore, the surface of the inorganic nanofiller is treated with a silane coupling agent.
[0023] The above fillers can enhance tensile strength and bonding strength, but the distribution density should not be too large or too small. Too little will be ineffective, and too large will have a negative effect. The particle size range is too large, the particle size is not concentrated, and the effect is not good. The more concentrated the particle size, the better. The absolute value of the particle size should not be too large or too small, and the particle size should be appropriate.
[0024] Furthermore, the material of the insulating support layer is selected from one of an organic polymer insulating material, an inorganic insulating material, and a composite material. Further preferably, the composite material is composed of an organic polymer insulating material and an inorganic insulating material.
[0025] Further, the organic polymer insulating material is selected from at least one of polyamide (PA), polyterephthalate (PET), polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PBT), polyparaphenylene terephthalamide (PPA), epoxy resin, polyoxymethylene (POM), phenolic resin, polypropylene (PPE), polytetrafluoroethylene (PTFE), silicone rubber, polyvinylidene fluoride (PVDF), polycarbonate (PC), aramid, polydimethylphenylene amine, cellulose and its derivatives, starch and its derivatives, protein and its derivatives, polyvinyl alcohol and its crosslinked products, polyethylene glycol and its crosslinked products. In an embodiment of the present application, the material of the insulating support layer is selected from organic polymer insulating materials. Since the density of the insulating support layer is usually smaller than that of metal, the current collector of the present application can not only improve the safety performance of the battery, but also help to improve the weight energy density of the battery. Furthermore, since the insulating support layer can play a good role in bearing and protecting the conductive layer on its surface, it is not easy to cause the pole piece fracture phenomenon commonly seen in existing metal foil current collectors.
[0026] Furthermore, the inorganic insulating material is preferably at least one of aluminum oxide (Al2O3), silicon carbide (SiC), and silicon dioxide (SiO2).
[0027] Furthermore, the composite material is selected from at least one of epoxy resin glass fiber reinforced composite materials and polyester resin glass fiber reinforced composite materials.
[0028] Furthermore, the insulating support layer contains reinforcing materials, such as non-woven fabrics, bulletproof vest threads or carbon fibers.
[0029] Furthermore, the insulating support layer also contains electronic conductive material.
[0030] Furthermore, the electronically conductive material includes one or more of metals, metal oxides and conductive carbon.
[0031] Furthermore, a conductive enhancement layer is partially or entirely provided on the side wall of the open structure, and the conductive enhancement layer is connected to the dense conductive layer.
[0032] Furthermore, a conductive enhancement layer is provided on the surface of the insulating support layer.
[0033] In the existing current collector scheme, since the insulating support layer is non-conductive and the conductive layer is relatively thin, the conductivity has become the "short board" of the existing composite current collector. In the embodiment of the present application, the present application makes the current collector thicker by setting an insulating support layer on the dense conductive layer, and the set conductive structure also extends to at least one surface of the insulating support layer and the hole wall surface of multiple holes, so that a three-dimensional, multi-point conductive network can be formed in the current collector, further improving the conductivity of the composite current collector, reducing the polarization of the pole piece and the battery, and improving the high-rate charge and discharge performance and cycle life of the battery.
[0034] Furthermore, the conductive enhancement layer is made of the same material as the dense conductive layer, and has a thickness of 10-100 nm.
[0035] Furthermore, the material of the dense conductive layer is selected from at least one of metal conductive materials and carbon-based conductive materials.
[0036] Furthermore, the metal conductive material is at least one selected from aluminum, copper, nickel, titanium, silver, nickel-copper alloy, and aluminum-zirconium alloy, and the carbon-based conductive material is at least one selected from graphite, acetylene black, graphene, and carbon nanotubes.
[0037] In an embodiment of the present application, the dense conductive layer is composed of a conductive material (such as a metal or a carbon nanomaterial) and is used for current concentration and transmission. The dense conductive layer has the following characteristics: (1) The densified conductive layer has a high-density structure with no or almost no pores or gaps, such as a metal foil, including a copper foil, an aluminum foil, etc. This high-density structure can effectively reduce resistance and provide a better current conduction path. (2) The densified conductive layer has a flat surface, which helps to ensure good contact and connectivity, reduce contact resistance, and provide uniform current distribution. (3) The densified conductive layer, such as a complete metal foil selected from aluminum foil, copper foil, etc., reduces the risk of the metal coating deposited in the existing composite current collector being easily destroyed due to the destruction of the polymer layer, so that the current collector of the utility model further combines the advantages of metal foil current collectors and conventional composite current collectors.
[0038] The preparation method of the composite current collector of the present application is: placing a dense conductive layer material such as aluminum or copper material in a roller press, continuously rolling the material into a dense conductive layer of desired thickness by rolling, and then thermally compounding with an insulating support layer of a certain thickness on both sides of the dense conductive layer by conventional dry compounding, wet compounding or solvent-free compounding. The insulating support layer can be pre-set with holes or punched after compounding to form a structure of an insulating support layer with through holes on both sides of the dense conductive layer; or forming an insulating support layer on the dense conductive layer by melt extrusion calendering, and then punching holes; the through holes on the insulating support layer can be obtained by laser drilling or the like.
[0039] On the other hand, the utility model provides a pole piece, comprising the current collector as mentioned above and an electrode active material layer formed on the surface of the current collector.
[0040] In a third aspect, the utility model provides an electrochemical device, comprising a pole piece as described above. The electrochemical device provided by the utility model includes an electrolyte, a negative pole piece, a separator and a positive pole piece. Specifically, the electrochemical device can be a wound or laminated battery, such as a lithium ion secondary battery, a lithium primary battery, a sodium ion battery, and a magnesium ion battery, but is not limited thereto.
[0041] The technical solution of the utility model has at least the following beneficial effects:
[0042] 1. The conductive layer of the utility model adopts less material and lighter weight, which can better reduce the weight of the current collector and the pole piece while providing better performance.
[0043] 2. The open structures of the technical solution of the utility model only penetrate the insulating support layers where they are located, and the dense conductive layer is complete. Therefore, on the one hand, the continuous conductive structure is retained. On the other hand, its conductive contact surface is the sum of the pore surface areas of the entire open structure, which is much larger than the cross-sectional area of the through hole. Therefore, under the premise of having higher mechanical properties and mechanical properties, the current collection and conductivity of the collector are greatly improved.
[0044] 3. In the technical solution of the utility model, multiple sub-support layers are provided in an insulating support layer with gradually increasing thickness from the inside to the outside, so that the bending stress of the insulating support layer is dispersed to each sub-support layer during bending, avoiding the requirement for the bending synchronization of the insulating support layer as a whole and the dense conductive layer. At the same time, since the thickness of the inner sub-support layer does not exceed half of the thickness of the dense conductive layer, it is easy to bend during the bending process of the dense conductive layer and keep consistent with the dense conductive layer, and becomes a bending buffer area between the insulating support layer and the dense conductive layer.
[0045] 4. In the technical solution of the utility model, an insulating support layer is provided on the surface of the composite current collector, and the provision of through holes can facilitate the passage of the electrolyte. The dendrites formed by the electrolyte in the conductive layer on the surface of the electrode will first be on the inside of the through holes. The provision of the through holes in the insulating support layer further reduces the probability of dendrite formation and penetration of the diaphragm.
[0046] 5. Compared with the traditional composite current collector, the hole wall of the insulating through hole of the present technical solution can be partially or completely provided with a conductive enhancement layer. This three-dimensional conductive structure setting further forms a three-dimensional conductive transmission path with higher conductivity.
[0047] 6. When punctured, traditional metal foil will produce larger ridges, which may pierce the diaphragm and cause a short circuit in the battery. The middle layer of the present application is a metal layer, and the two sides are polymer material layers, which can effectively absorb deformation stress. When punctured, the ridges produced by the metal foil are smaller in size, and due to the restrictiveness of the outer base film, they are all confined inside the current collector, further reducing the risk of short circuit in the battery.
[0048] 7. The key steps in the preparation of conventional composite current collectors are vacuum magnetron sputtering and water plating. The vacuum magnetron sputtering process has high requirements for equipment, and the efficiency of magnetron sputtering copper deposition is relatively low. The composite current collector in the utility model can be composited with organic materials on the basis of metal copper, metal aluminum, etc. formed by conventional roll forming, and the preparation process is relatively simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a cross-sectional view of the pole piece prepared by the utility model.
[0050] Among them: 1. dense conductive layer; 2. insulating support layer; 3. through-hole; 4. active material layer; 5. conductive enhancement layer. DETAILED DESCRIPTION
[0051] The utility model can be implemented through the following specific implementation scheme:
[0052] Example 1 Preparation of composite current collector
[0053] 1.1 Place the aluminum or copper material in a roller press, and continuously roll the material into a dense conductive layer (i.e., aluminum foil, copper foil) of the required thickness by rolling, and then thermally compound with one or two layers of PP film or PET film of a certain thickness on both sides of the dense conductive layer by conventional dry compounding, and then set through holes on the PP film or PET film by laser punching (control the laser conditions to form holes only on the film) to form a positive electrode current collector or a negative electrode current collector having an insulating support layer with through holes on both sides of the dense conductive layer: the shape of the hole is circular, the hole diameter is 0.01 mm, the volume proportion θ of the hole is 60% (except for Examples 1b and 2b, which is 20%), and the spacing between the holes is 0.2 mm. When the sublayer of the insulating support layer has nano inorganic fillers, the nano inorganic fillers are dispersed in ethanol (0.1 g / mL, the slurry contains 2 wt% of film-forming agent ethyl cellulose), and then coated on the surface of one of the sublayers. Two or more sublayers are stacked and then composited onto the dense conductive layer.
[0054] 1.2 Take the current collector prepared in 1.1, and deposit a conductive enhancement layer on the surface of the insulating support layer, the wall surface of the through hole or the wall surface of the through hole, and the surface of the insulating support layer by vacuum evaporation, wherein the positive electrode current collector deposition material is aluminum, the negative electrode current collector deposition material is copper, and the thickness of the conductive enhancement layer is 100nm. The positive and negative electrode current collectors are shown in Tables 1 and 2 below.
[0055] Table 1 Positive electrode current collector
[0056]
[0057] In the above table, the volume proportion θ of the through hole in Example 1b in the insulating support layer is 20%, and the rest is 60%, and a 100nm thick aluminum conductive reinforcement layer is set on the hole wall surface of Example 1b, and the bottom is in contact with the aluminum foil layer. Comparative Example 1a is a conventional aluminum foil current collector, and Comparative Example 1b is a sample with an existing composite current collector structure obtained by evaporating a 1μm thick aluminum layer on both sides of a 2μm thick PET film (polyethylene terephthalate), and in Comparative Example 1c, the through hole penetrates the PET layers on both sides and the aluminum foil layer in the middle.
[0058] Table 2 Negative electrode current collector
[0059]
[0060] In the above table, the volume proportion of the through hole in Example 2b in the insulating support layer is 20%, and the rest is 60%, and a 100nm thick copper conductive reinforcement layer is set on the hole wall surface of Example 2b, and it is in contact with the copper foil layer. Comparative Example 2a is a conventional aluminum foil current collector, and Comparative Example 2b is a sample with an existing composite current collector structure obtained by magnetron sputtering 50nm copper layers on both sides of a 2μm PP (polypropylene) film, and then electroplating the thickened copper layer to 1μm. In Comparative Example 2c, the through hole penetrates the PP layers on both sides and the copper foil layer in the middle.
[0061] Example 2 Preparation of pole piece
[0062] Through conventional battery coating process, positive electrode slurry or negative electrode slurry is coated on the surface of current collector, and after drying at 100°C, positive electrode sheet or negative electrode sheet is obtained. Figure 1 As shown, it includes a dense conductive layer 1, an insulating support layer 2, a through hole 3 and an active material layer 4, and the pole piece containing the current collector embodiment 1b and embodiment 2b is also provided with a conductive enhancement layer 5, and the conductive enhancement layer 5 is arranged on the corresponding current collector embodiment 1b and embodiment 2b. Wherein:
[0063] The active material of the positive electrode plate is ternary nickel-cobalt-manganese-lithium slurry NCM523 (NCM523: PVDF: Ketjen black = 90:5:5, NMP is the solvent, solid content 60%), and the pressing thickness of the positive electrode active material layer is 15 μm;
[0064] The active material of the negative electrode plate is graphite (graphite: SBR: ultrafine graphite = 92:6:4, NMP is the solvent, and the solid content is 46%), and the pressing thickness of the negative electrode active material layer is 15 μm.
[0065] Example 3: Preparation of battery:
[0066] Through the conventional battery manufacturing process, the positive electrode sheet (compacted density: 3.4g / cm 3 ), PP / PE / PP separator and negative electrode sheet (compacted density: 1.6g / cm 3 ) are wound together into a bare battery cell, which is then placed in a battery casing and injected with electrolyte (EC:EMC volume ratio is 3:7, LiPF6 is 1 mol / L), followed by sealing, formation and other processes to finally obtain a secondary battery.
[0067] Performance Testing
[0068] 1. Current collector tensile test
[0069] According to the tensile test method in GB / T228.1-2010, the current collector sample length is 200±2mm, the width is 15±0.25mm, the tensile speed is set to 50mm / min, the distance between the chucks of the testing machine is 125±0.1mm, the sample is stretched to break and the test is stopped, the tensile strength is obtained, and the tensile strength multiple strength relative to the aluminum foil or copper foil is calculated, 5 parallel samples are tested, and the average value is taken as the test result. The test results are shown in Table 3-4.
[0070] Table 3
[0071] serial number Relative tensile strength of comparative example 1a Example 1a 1.08 Example 1c 1.12
[0072] It can be seen from the table that the composite current collector with an open structure prepared in the present application can obtain better tensile properties when the aluminum foil conductive layer is thinner.
[0073] Table 4
[0074] serial number Relative tensile strength multiple of comparative example 2a Example 2a 1.07 Example 2c 1.09
[0075] It can be seen from the above table that the copper negative electrode current collector prepared in the present application can obtain tensile properties comparable to those of traditional copper foil or composite current collectors when the copper layer is thinner.
[0076] 2. Secondary battery cycle capacity test
[0077] At 25℃ and 45℃, the lithium-ion secondary battery is charged to 4.2V at a constant current rate of 1C, then charged at a constant voltage until the current is less than or equal to 0.05C, and then discharged to 2.5V at a constant current rate of 1C. This is a charge and discharge cycle. The discharge capacity of this time is the discharge capacity of the first cycle. Repeat the above heavy discharge cycle and record the capacity retention rate after 1000 cycles. The test results are shown in Table 5:
[0078] Table 5
[0079]
[0080] From the comparison of batteries 2-6, 13-17 with batteries 1, 7-12, and 18-23 in the above table, it can be seen that the current collector prepared based on the scheme of the present application has good electrical properties at both room temperature and high temperature, and can further improve the cycle capacity of the battery. When the thickness of the polymer insulating support layer is increased within a certain range, such as the comparison between battery 2 and battery 4, battery 13 and battery 15, the cycle capacity of the battery at different temperatures can be further enhanced, and the effect of temperature on the cycle capacity can be reduced. When the polymer insulating support layer is set to multiple sublayers, and the thickness of the internal sublayer is thin, the cycle performance and temperature resistance of the current collector can be enhanced, see the comparison between battery 5 and battery 4, battery 16 and battery 15. However, if the thickness of the innermost sublayer is thicker than the dense conductive layer, such as battery 9 or battery 20, or when the difference between the inner and outer sublayers is too large (more than 2 times), such as battery 10 or battery 21, the setting of the sublayer is reduced for the battery performance improvement ability. Arranging nano inorganic particles between the two sublayers can improve the heat resistance of the current collector, as shown in battery 6 and battery 17, the difference in cycle capacity at high temperature and room temperature is less than that of battery 5 and battery 16. However, further research has found that this enhancement effect is closely related to the particle size of the nanoparticles. When the particle size of the nanoparticles is small, there is basically no enhancement effect, as shown in battery 11 and battery 22, and when the particle size of the nanoparticles is large, it has an adverse effect. Under the scheme of this application, the suitable particle size range of the nanoparticles is 80-150nm. At the same time, it can be seen from the comparison of battery 2 and battery 8, battery 13 and battery 19 that under the scheme conditions of this application, avoiding the perforation of the metal foil layer and the rubber can obtain similar cycle capacity, especially the cycle performance is equivalent at high temperature.
[0081] 3. Impedance test
[0082] The DC internal resistance DCR of battery 13 and battery 19 is tested as follows:
[0083] The battery is charged under a certain pulse current, and then discharged at the same pulse time under the pulse current after standing for 30 minutes. After completing one pulse charge and discharge, the pulse time is kept unchanged, and the pulse current is increased to repeat the charge and discharge. The pulse currents are: 1mA, 3mA, 5mA, 7mA, 9mA, and the pulse time is 1s. The voltage difference ΔU before and after the battery has different current pulses is recorded, and the voltage and current are linearly fitted. The slope is the DC internal resistance DCR.
[0084] The measured DCR of battery 13 is 0.978Ω, and the DC internal resistance of battery 19 is 1.046Ω. It can be seen that the DC internal resistance of battery 13 is reduced by 6.5% compared with battery 19.
[0085] The above implementation is only the best implementation of the utility model and has no limiting effect on the protection scope of the utility model. All non-substantial changes and adjustments made by technical practitioners in this professional field on the basis of the utility model are within the protection scope claimed by the utility model.
Claims
1. A current collector having an open structure, characterized in that: The dense conductive layer comprises an insulating support layer on both sides of the dense conductive layer opposite to each other in the thickness direction. The insulating support layer has an open structure which penetrates the insulating support layer along the thickness direction of the insulating support layer.
2. The current collector according to claim 1, characterized in that: The thickness D1 of the dense conductive layer is 0.5 μm-10 μm; The thickness D2 of the insulating support layer is 1 μm-10 μm.
3. The current collector according to claim 1 or 2, characterized in that: The volume proportion θ of the open structure in the insulating support layer satisfies 0.1≤θ≤0.
8.
4. The current collector according to claim 1, characterized in that: The open structure is a quadrilateral, circular or quasi-circular hole.
5. The current collector according to claim 4, characterized in that: The inner diameter or side length of the open structure is 1 μm-3 mm.
6. The current collector according to claim 4, characterized in that: The distance between the open structures is 0.01 mm to 5 mm; The spacing is distributed in an equidistant or non-equidistant manner.
7. The current collector according to claim 1, characterized in that: The insulating support layer includes N sub-support layers, where N is an integer greater than or equal to 2, wherein the first sub-support layer is connected to the dense conductive layer, and the thickness dn of each sub-support layer gradually increases from the first sub-support layer to the Nth sub-support layer.
8. The current collector according to claim 7, characterized in that: When N is an even number, the sum of the thicknesses of the 1st to N / 2 sublayers is d N / 2 Satisfy 0.1*D1≤d N / 2 ≤0.5*D1; When N is an odd number, the sum of the thicknesses of the 1st to (N-1) / 2nd sublayers is d N-1 / 2 Satisfy 0.08*D1≤d N-1 / 2 ≤0.4*D1.
9. The current collector according to claim 7, characterized in that: The thickness of two adjacent sub-support layers differs by 1-2 times.
10. The current collector according to claim 7, characterized in that: Nano inorganic fillers are also distributed on the contact interface of each sub-support layer, and the distribution density of the nano inorganic fillers is 0.05-0.1g / cm 3 .
11. The current collector according to claim 10, characterized in that: The particle size of the nano inorganic filler is in the range of 80-150 nm.
12. The current collector according to claim 10, characterized in that: The nano inorganic filler is one or more of nano silicon dioxide, nano kaolin and nano barium sulfate.
13. The current collector according to claim 10, characterized in that: The surface of the nano inorganic filler is treated with a silane coupling agent.
14. The current collector according to claim 1 or 2, characterized in that: A conductive reinforcement layer is partially or entirely provided on the side wall of the open structure, and / or a conductive reinforcement layer is also provided on the surface of the insulating support layer; The conductive enhancement layer arranged on the side wall of the open structure is connected to the dense conductive layer.
15. The current collector according to claim 14, characterized in that: The conductive reinforcement layer is made of the same material as the dense conductive layer. And / or, the thickness of the conductive enhancement layer is 10-100 nm.
16. A pole piece, characterized in that: The invention comprises the current collector according to any one of claims 1 to 15 and an electrode active material layer formed on the surface of the current collector.
17. An electrochemical device, characterized in that: The invention comprises an electrolyte, a separator and the pole piece as claimed in claim 16.
Citation Information
Patent Citations
Current collector and preparation method thereof, negative electrode and electrochemical energy storage device
CN115440987A